Whether the Indications for Reverse Shoulder Arthroplasty Should Continue to Be Expanded? A Systematic Review and Meta‐Analysis - Huankun Li; Hangsheng Bao; Zhidong Yang; Baijun Hu; Yaocheng Pan; Yi Wang; Jiayi Chen; Hongjun Chen; Bisheng Shen; Yonggen Zou (Orthopaedic Surgery)
ABSTRACT Background It is still unclear whether reverse total shoulder arthroplasty (RTSA) has advantages over traditional hemiarthroplasty (HA) and anatomic total shoulder arthroplasty (ATSA) in the treatment of complex shoulder joint diseases. Therefore, this study aims to evaluate the clinical effectiveness of RTSA in the treatment of complex shoulder joint diseases and further determine whether it is necessary to expand the indications of RTSA. Method We conducted a systematic search of studies published between January 1, 2012 and May 31, 2023 in PubMed, Embase, and Cochrane databases. The experimental group included patients who underwent primary reverse total shoulder arthroplasty (RTSA), while the control group consisted of patients who underwent primary hemiarthroplasty (HA) or anatomic total shoulder arthroplasty (ATSA). The minimum follow‐up period was 1 year, and a random‐effects model was utilized for data synthesis. Results A total of 45 studies were included in the meta‐analysis. Compare to HA, RTSA showed significant advantages in postoperative ASES scores (p = 0.004), forward flexion (p < 0.0001), and abduction (p < 0.0001). Compare to ATSA, RTSA showed significantly lower postoperative Constant scores (p = 0.004), ASES scores (p = 0.001), SST scores (p < 0.0001), forward flexion (p < 0.0001), abduction (p = 0.011), internal rotation (p < 0.0001), and external rotation (p < 0.0001). Further meta regression analysis was conducted, considering factors such as region, age, gender ratio, and follow‐up time, excluding the influence of relevant factors. Overall, RTSA did not demonstrate advantages in postoperative functional scores and range of motion. In terms of complication and revision rates, RTSA had lower rates compared to HA and ATSA, except for the complication rate, where there was no significant difference between RTSA and ATSA (p = 0.521), but statistically significant differences were observed in other measures. Conclusion RTSA demonstrates better clinical efficacy compared to HA but is inferior to ATSA. It can be considered for expanding treatment options for elderly patients with 3 or 4‐part proximal humeral fractures, but it is not suitable for treating end‐stage shoulder arthritis and humeral head necrosis. Overall, the decision to use RTSA should be carefully evaluated based on the extent of the patient's rotator cuff injury.